Regulating Climate Change - Bialowas, Angelika (Kent Law Review, 2014)
Concerns about global climate change have led to international and national commitments to reverse the growth of greenhouse gas emissions. Given the range and complexity of the climate issue, solutions are required at all levels, shifting the regulatory architectures of the environmental system and the traditional configuration of the state. A critical examination reveals a move away from the sovereign into a polycentric arrangement that, as a result, raises questions as to what is meant by regulation and regulatory activities. Any effort to address climate change raises the question of regulation, and yet this area remains unexplored. This should prompt serious concern for current and future climate change scholarship, which addresses the issues at stake, yet fails to delve into the foundations of climate change governance. This paper attempts to fill this void through an interdisciplinary approach to climate change, using the Kyoto Protocol as the prevailing example.